2015
DOI: 10.1590/0102-311x00101214
|View full text |Cite
|
Sign up to set email alerts
|

Do que morrem os pacientes com tuberculose: causas múltiplas de morte de uma coorte de casos notificados e uma proposta de investigação de causas presumíveis

Abstract: O objetivo deste trabalho foi analisar as causas múltiplas de morte de uma coorte de pacientes notificados com tuberculose (TB) e apresentar uma proposta de investigação de causas presumíveis. Realizou-se linkage probabilístico entre o Sistema de Informação de Agravos de Notificação (SINAN) 2006 e o Sistema de Informação sobre Mortalidade (SIM), 2006-2008. Ocorreram 825 mortes, das quais 23% por TB, 16% com TB e 61% sem menção da TB. Duzentos e quinze (42,7%) óbitos ocorreram antes do término do esquema básico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
18

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 23 publications
5
31
0
18
Order By: Relevance
“…HIV disease was by far the most frequent underlying cause of deaths in which tuberculosis was reported as an associate cause, followed by diseases of the respiratory and cardiovascular systems, neoplasms, nutritional and metabolic disorders and digestive diseases. Similar cause specific mortality profiles were found in two cohort studies involving tuberculosis patients in Brazil and China [13,21].…”
Section: Discussionsupporting
confidence: 80%
“…HIV disease was by far the most frequent underlying cause of deaths in which tuberculosis was reported as an associate cause, followed by diseases of the respiratory and cardiovascular systems, neoplasms, nutritional and metabolic disorders and digestive diseases. Similar cause specific mortality profiles were found in two cohort studies involving tuberculosis patients in Brazil and China [13,21].…”
Section: Discussionsupporting
confidence: 80%
“…A study developed with Rio de Janeiro, RJ, residents revealed that tuberculosis is the main cause of death for approximately 25% of patients reported with the disease two years after the diagnosis, and the main reasons include discontinuation of treatment, which increases the number of deaths and persists as a problem in the country 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Paraná has 399 municipalities distributed in 22 . For being data available on official databases of free access, the absence of ethical appraisal is justified.…”
Section: Methodsmentioning
confidence: 99%
“…Estudo que analisou as causas múltiplas de morte de uma coorte de pacientes com tuberculose encontrou maior frequência de óbitos nos idosos. 21 Outros autores também têm encontrado associação de faixas etárias mais elevadas com óbito, porém para o desfecho abandono tem sido descrita associação com faixa etária de adulto jovem, relacionada talvez a fatores sociais, etilismo e drogas. 8,9,20,22,23 A raça/cor de pele referida como não branca apresentou 1,6 vezes mais chances de ter o desfecho desfavorável em relação à branca.…”
Section: Fatores Associados Ao óBito E Ao Abandono Do Tratamento Da Tunclassified